Appraisal and repair of existing concrete structures - Kog, Yue Choong (ICE Publishing, 2023)
Appraisal and Repair of Existing Concrete Structures is a practical guide for civil and structural engineers involved in the preservation, renovation and repair of concrete buildings and structures. Comprehensive in scope, the book contains detailed guidance on all stages of appraisal, including common issues that arise, and how to address gaps within current codes of practice.